2021
DOI: 10.3389/fphar.2021.787193
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Tears and Saliva From Sjogren’s Syndrome Patients

Abstract: Sjogren’s syndrome (SS) is characterized by dysfunctional mucous membranes and dysregulated moisture-secreting glands resulting in various symptoms, including dry mouth and dry eyes. Here, we wanted to profile and compare the tear and saliva proteomes of SS patients to healthy controls. Tear and saliva samples were collected and subjected to an isotopic dimethylation labeling shotgun proteomics workflow to identify alterations in protein levels. In tear samples, we identified 83 upregulated and 112 downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 84 publications
1
32
1
Order By: Relevance
“…Tear proteomic analysis by Das et al [ 20 ] using high performance liquid chromatography (HPLC) and mass spectrometry revealed the upregulation of 83 proteins and downregulation of 112 proteins in pSS patients compared to HCs. Enrichment pathway analysis of upregulated proteins included leukocyte trans-endothelial migration, protein-lipid complex remodelling and collagen catabolic pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tear proteomic analysis by Das et al [ 20 ] using high performance liquid chromatography (HPLC) and mass spectrometry revealed the upregulation of 83 proteins and downregulation of 112 proteins in pSS patients compared to HCs. Enrichment pathway analysis of upregulated proteins included leukocyte trans-endothelial migration, protein-lipid complex remodelling and collagen catabolic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…However, none of the protein biomarkers correlated with saliva flow rates in pSS. A more recent study by Das et al [ 20 ] identified the upregulation of 104 proteins and downregulation of 42 proteins in pSS compared to controls. Some enriched pathways in patients’ saliva included JAK-STAT signalling after IL-12 stimulation, superoxide metabolic process and phagocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Conditioned media samples from 24 hours after the completion of loading were analyzed for PRG4 concentration using the AlphaLISA platform (PerkenElmer), as described previously [ 47 ]. Briefly, streptavidin modified donor beads were bound to biotin-labeled recombinant human PRG4 (Lubris BioPharma, Naples, FL) [ 48 ], and anti-PRG4 mAb 94D6 was bound to acceptor beads.…”
Section: Methodsmentioning
confidence: 99%
“…Conditioned media samples from 24 hours after the completion of loading were analyzed for PRG4 concentration using the AlphaLISA platform (PerkenElmer), as described previously [45]. Briefly, streptavidin modified donor beads were bound to biotin-labeled recombinant human PRG4 (Lubris BioPharma, Naples, FL) [46], and anti-PRG4 mAb 94D6 was bound to acceptor beads.…”
Section: Methodsmentioning
confidence: 99%